Student Engagement as a Factor of Successful Online Course Completion - Pascal Roubides; Adwyn Roubides (Scientia Publica Media, 2025)
The following monogram discusses a quantitative case study funded via a grant award which was aimed at discovering correlations of course access levels and academic success in an online gateway mathematics course at a higher education institution in south Florida, USA. In particular, the study aimed at investigating whether student engagement in a general education online mathematics course, College Algebra, as measured by the frequency of student course logins, might correlate with successful completion of the course itself. The study addresses the need for quantitative measures to identify at-risk student behaviors in online learning environments, where subjective faculty judgment often delays or limits effective interventions. Results obtained show a positive correlation between the frequency of student course logins and their respective final course outcomes. Despite challenges accessing a higher level of detailed course engagement data, as initially intended, the study results statistically support the hypothesis that increased course access correlates with better academic outcomes. The study also aligns with activity theory, which emphasizes that meaningful learning arises from active engagement, as well as with recent studies on student engagement challenges in online learning. It is the author’s point of view that the current study is an important first step in statistically quantifying such expected relations and promoting further study and application of quantitative metrics in regards to addressing online students’ course engagement challenges and hopefully lead to early warning systems that can increase timely interventions, and by extension, increase overall rates of student retention and success in online environments.